2022
DOI: 10.1002/adfm.202210485
|View full text |Cite
|
Sign up to set email alerts
|

3D‐Printed Stacked Ionic Assemblies for Iontronic Touch Sensors

Abstract: Sensing is the process of detecting and monitoring any physico-chemical environmental parameters. Herein, new self-powered iontronic sensors, which utilize touch-induced ionic charge separation in ionically conductive hydrogels, are introduced for potential use in object mapping, recognition, and localization. This is accomplished using high-resolution stereolithography (SLA) 3D printing of stacked ionic assemblies consisting of discrete compartments having different ion transport properties. The latter assemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 61 publications
(47 reference statements)
1
16
0
Order By: Relevance
“…[5] Last year, Dobashi et al [6] investigated pressure-induced ionic current in a polyacrylamide hydrogel, this phenomenon is called piezoionic effect, [7] referring to ionic soft materials that can generate electrical output under pressure. [8] Recently, Odent et al [9] reported a 3D-printed stacked hydrogel shows large piezoionic output. This effect provides a new idea for the development of highly sensitive hydrogel sensors.…”
Section: Doi: 101002/adfm202300701mentioning
confidence: 99%
See 1 more Smart Citation
“…[5] Last year, Dobashi et al [6] investigated pressure-induced ionic current in a polyacrylamide hydrogel, this phenomenon is called piezoionic effect, [7] referring to ionic soft materials that can generate electrical output under pressure. [8] Recently, Odent et al [9] reported a 3D-printed stacked hydrogel shows large piezoionic output. This effect provides a new idea for the development of highly sensitive hydrogel sensors.…”
Section: Doi: 101002/adfm202300701mentioning
confidence: 99%
“…[ 8 ] Recently, Odent et al. [ 9 ] reported a 3D‐printed stacked hydrogel shows large piezoionic output. This effect provides a new idea for the development of highly sensitive hydrogel sensors.…”
Section: Introductionmentioning
confidence: 99%
“…250–252 Hydrogels have recently gained significant attention in the domain of artificial skin due to their resemblance to human tissues, since these materials are soft, high-water content, flexible, wearable and show high biocompatibility. 253–255 The majority of hydrogel-based sensors are piezoresistive, based on the principle that the electrical resistivity of a material changes when mechanical strain is applied. 256–258 However, piezoresistive hydrogels show several disadvantages, including an apparent hysteresis effect, low mechanical durability, ease of temperature variations, and the prerequisite for an external source of power, which pose significant barriers to practical application.…”
Section: Flexible Electronic and Bio-medical Applications Of P-pegsmentioning
confidence: 99%
“…Recently ionic systems have been broadly investigated due to the increased demand for neuromorphic applications, new computing methods, and less energy consumption 2 . Different iontronic devices based on the concept of transmitting, generating or storing signals by ions were developed in the last years [3][4][5][6][7][8][9][10][11][12] . The electric double layer (EDL) formation at the interface between two different materials is considered one of the important processes in iontronics.…”
Section: Introductionmentioning
confidence: 99%